Regulation of mammalian cell division by the chromosomal passenger complex - Lens, Susanne (Henry Stewart Talks, 2009)
Cell division, Cancer and chromosomal instability, Cell division errors and aneuploidy, The chromosomal passenger complex (CPC), The CPC executes various functions in the dividing cell, Regulation of Aurora B kinase activity and localization, Centromeres and kinetochores, Perturbation of the CPC results in severe chromosome congression and segregation defects, Requirements for faithful chromosome segregation, The CPC promotes bi-orientation by influencing kinetochore-microtubule interactions, CPC substrates at the kinetochore, Hec1/Ndc80, The CPC is essential for a functional mitotic checkpoint, The dynamic localization at centromeres, Transfer to the central spindle, The CPC and cytokinesis, Aurora kinase inhibitors as anti-cancer drugs